Mandated Corporate Social Responsibility in Nepalese Commercial Banks: A Qualitative Perspective - Aryal, Bibek; Danuwar , Ranjana Kumari; Timsina , Baburam (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: CSR has been traditionally viewed as a voluntary undertaking; however, in recent times, CSR has become mandatory as per the Nepal Rastra Bank directive. This study investigates the status of mandated Corporate Social Responsibility in Nepalese Commercial Banks, how Nepalese banks are practicing, perceiving, and facing challenges with mandated CSR policies/regulations. Design/methodology/approach: This study uses qualitative content analysis, using the NVIVO 14 software to measure the banking CSR reporting practices, regulatory response, and challenges in implementing CSR initiatives. Findings: The finding reveals that banks are implementing CSR guidelines/rules set by the Nepal Rastra Bank and the Industrial Enterprise Act. Similarly, banks are facing problems such as finding suitable CSR Projects, group finding and Issues with regulatory planning timelines, and suggestion for more effective monitoring. Conclusion: Regulatory frameworks, particularly those mandated by the NRB and IEA, were found to provide strategic clarity. However, their rigid implementation, such as restrictions on partnerships and inflexible fund allocation, limits innovation, disrupts strategic alignment, and impedes high-impact interventions. Implications: The study highlights the urgent need to rethink CSR beyond compliance. Managers must transition from procedural reporting toward impact-driven strategies that reflect genuine community needs. Investment in impact measurement frameworks and stakeholder feedback loops will enhance both credibility and value creation. Originality/value: This study is not published in another journal and provide a new value in context of CSR. JEL Classification: M14, O35, D91, E58